Evaluation of herbicides for selective weed control in cutleaf groundcherry (Physalis angulata L.). (July 2023) - Khodadadi, Vahid; Yousefi, Ali Reza; shahbazi, Saeid; Heydari, Moslem; Kanatas, Panagiotis; Tataridas, Alexandros; Travlos, Ilias
Abstract: Cultivation of cutleaf groundcherry ( Physalis angulata L.) is increasing due to its potential nutritional and medicinal use. Lack of registered herbicides is a main constrain for efficient weed control and consequently successful production in cutleaf groundcherry. To evaluate the efficacy of eight herbicide treatments for weed control and crop injury in cutleaf groundcherry, field experiments were conducted in two consequent years (2017 and 2018). Treatments consisted of PRE application of pendimethalin and POST application of foramsulfuron, oxadiazon, nicosulfuron, rimsulfuron, sulfosulfuron, iodosulfuron-methyl-sodium + mesosulfuron-methyl-sodium + mefenpyr-diethyl (IMM), and iodosulfuron-methyl-sodium + mesosulfuron-methyl-sodium + diflufenican (IMD). Weed-free and weedy plots were also considered for comparison in both years. Although, density and biomass of broadleaf weeds were decreased in all treatments compared to the weedy check, grass weeds did not affect by the herbicides. In both years, the lowest broadleaf weed dry weight of (12 g m −2 ) was found in plots treated by IMD and IMM. Different levels of herbicide injury was found in cutleaf groundcherry plants. Of the herbicides tested, the minimum crop injury was related to plots treated with foramsulfuron (1.4%), rimsulfuron (2.7%) and sulfosulfuron (6%). Notice that the yield in rimsulfuron treatment (38, 160 kg ha -1 and 18, 053 kg ha -1 in 2017 and 2018) was just about 62% and 48% of that in weed free treatment in 2017 and 2018, respectively, although rimsulfuron treatment improved crop fruit yield compared with the weedy treatment. Overall, although none of the tested herbicides could provide fruit yield similar to the weed free condition, an herbicide program consisting of rimsulfuron and sulfosulfuron would therefore provide both high weed control and crop safety. Graphical abstract: Image 1 Highlights: Herbicides for weed control with high crop safety in P.angulata was studied in two years. Oxadiazon and pendimethalin showed severe injury to P.angulata . Lower injury on crop was observed in rimsulfuron and sulfosulfuron plots. Sulfosulfuron and rimsulfuron possesses potential for the management of weeds in P.angulata .